Intellectual Property in Malaysia: Initiatives, Challenges & Real Infringement Cases - Johari, Razana Juhaida (Economic affairs (Calcutta), 2023)
"The Industrial Revolution 4.0 has improved economic and societal well-being in Malaysia, and this has necessitated creativity and invention, which has resulted in the development of intellectual property. Intellectual property rights (IPR), which include patents, copyrights, designs rights, and trademarks, are largely responsible for providing incentives and protections for creative inventions. Yet, disputes between the parties at the time of IP registration and at a later stage still occur despite the intellectual property protection being in place. Hence, this study attempts to shed light on the numerous IPR activities taken by the Malaysian government, as well as on IPR challenges, their preventative measures, and actual infringement instances. Scopus, Web of Science, Science Direct, and Google Scholar were only a few of the databases that were examined to compile the literature on the subject from 2005 to 2021. This article contributes to the public’s knowledge and comprehension of intellectual property in Malaysian business, particularly in terms of its practices and difficulties."